Daycare Centres Learning Management Training in Sleman, Yogyakarta - Cholimah, Nur; Muthmainah, Muthmainah; Ningrum, Eka Sapti Cahya; Prayitno, Prayitno (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
This training was carried out to provide additional assistance and understanding in This training was carried out to provide assistance in overcoming learning management problems experienced by daycare managers in Depok, Sleman. This training was attended by 28 managers and teachers from each daycare institution. The training was carried out with mentoring and FGD. The results of the training showed that the level of satisfaction of the trainees with the material delivered by the resource persons was in the range of quite informative to very informative. The very informative category was felt by 58.82% of the trainees, 30.88% informative, and 10.3% quite informative. The most improved aspects are providing stimulation for children, curriculum development, and lesson plans. Even so, the problems that are still felt by the managers and teachers of daycare institutions include the understanding of the Merdeka Curriculum at daycare and the reference of its learning design, as well as the habituation of stimulation variations for children. The results show that there is a need for continuous training to support the creation of quality PAUD services, especially DAYCARE. The training provided may vary, but it is related to the management of learning in PAUD.